Romantisme Kereta Angin (Sepeda Onthel) di Yogyakarta Tahun 1970an - Puji Rahayu (Lembaran Sejarah, 2020)
This article examines the use of bicycle as public transport in the city of Yogyakarta during the 1970s. In the early years following Indonesian independence, the Indonesian society resumed its daily, peaceful life now with a new hope of economic and social prosperity as promised by the freedom from colonialism. In the city of Yogyakarta, the independent period of the 1970s was marked by the widespread use of bicycle as a public transport so immensely that the city got a reputation as a bicycle city. This article shows that while the widespread distribution of bicycle in Yogyakarta during the time was widespread, it still retained a social status. Bicycle was a symbol that erased colonialism as its use in the 1970s was not associated with the European elitism anymore. However, at the same time it showed a social chasm in the Yogyakarta society as only a small number of people, mostly government officials and university students, could afford it. In the 1970s city of Yogyakarta, bicycle functioned both as a symbol of freedom and as a mark of social divide.